2023
DOI: 10.1002/anse.202300063
|View full text |Cite
|
Sign up to set email alerts
|

Structural Elucidation and Relative Quantification of Fatty Acid Double Bond Positional Isomers in Biological Tissues Enabled by Gas‐Phase Charge Inversion Ion/Ion Reactions

Julia R. Bonney,
Boone. M Prentice

Abstract: Fatty acids (FAs) contain a vast amount of structural diversity, and differences in fatty acid structure have been associated with various disease states. Accurate identification and characterization of fatty acids is critical to fully understand the biochemical roles these compounds play in disease progression. Conventional tandem mass spectrometry (MS/MS) workflows do not provide sufficient structural information, necessitating alternative dissociation methods. Gas‐phase charge inversion ion/ion reactions ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 81 publications
(165 reference statements)
0
2
0
Order By: Relevance
“…Gas-phase cross-linking ion/ion reactions were performed via software modifications to the existing electron transfer dissociation (ETD) capability of the commercial FT-ICR MS (Scheme ). , Briefly, MALDI-generated sulfo-EGS cross-linker anions (1.5 s) and ESI-generated multiply charged ubiquitin cations ([M + 8H] 8+ ) (500 ms) were sequentially isolated via the quadrupole mass filter (QMF) and injected into the hexapole ion trap (Scheme a,b). A mutual storage ion/ion reaction period (1500 ms) of the oppositely charged reactant ions produced long-lived, charge-reduced complex cations with varying numbers of cross-linkers attached (Scheme c).…”
Section: Methodsmentioning
confidence: 99%
“…Gas-phase cross-linking ion/ion reactions were performed via software modifications to the existing electron transfer dissociation (ETD) capability of the commercial FT-ICR MS (Scheme ). , Briefly, MALDI-generated sulfo-EGS cross-linker anions (1.5 s) and ESI-generated multiply charged ubiquitin cations ([M + 8H] 8+ ) (500 ms) were sequentially isolated via the quadrupole mass filter (QMF) and injected into the hexapole ion trap (Scheme a,b). A mutual storage ion/ion reaction period (1500 ms) of the oppositely charged reactant ions produced long-lived, charge-reduced complex cations with varying numbers of cross-linkers attached (Scheme c).…”
Section: Methodsmentioning
confidence: 99%
“…Gas-phase cross-linking ion/ion reactions were performed via software modifications to the existing electron transfer dissociation (ETD) capability of the commercial FT-ICR MS (Figure 1). 49,[51][52][53][54][55] Briefly, MALDI-generated sulfo-EGS cross-linker anions (1 second) and ESI-generated multiply charged ubiquitin cations ([M + 8H] 8+ ) (500 milliseconds) were sequentially isolated via the quadrupole mass filter (QMF) and injected into the hexapole ion trap (Figure 1a and 1b). A mutual storage ion/ion reaction period (1,500 ms) of the oppositely charged reactant ions produced long-lived, charge-reduced, electrostatic complex cations with varying numbers of cross-linkers attached (Figure 1c).…”
Section: Ion/ion Reactionsmentioning
confidence: 99%
“…It has been revealed that lipid structure features such as headgroup, unsaturation degree, CC locations, and fatty acyl sn -positions are closely associated with lipid functions. Tandem mass spectrometry (MS/MS) has been widely used in lipidomics for the identification of molecular species information on complex lipids. However, it still remains challenging to unambiguously identify lipid CC location isomers or sn -position isomers in biological samples. In recent years, the development of novel dissociation methods such as ozone-induced dissociation (OzID), , electron impact excitation of ions from organics (EIEIO), and ultraviolet photodissociation (UVPD) , enabled identification of detailed structural information on intact lipids by MS. To avoid modification on mass spectrometers, some chemical modification strategies have been developed to identify detailed structures of lipids by collision-induced dissociation (CID) MS 2 , such as the Paternò–Büchi (PB) reaction, epoxidation, , ion/ion reactions, and singlet-oxygen ene reaction. , On being coupled with ESI-MS/MS, these methods were able to identify sn - or CC location isomers of several classes of lipids in tissue and biofluid extracts. , …”
Section: Introductionmentioning
confidence: 99%